Kajian Antrian Pelayanan Pendaftaran Pasien BPJS di Rumah Sakit - Heryana, Ade; Mahadewi, Erlina Puspitaloka; Ayuba, Iyan (Gorontalo Journal of Public Health, 2019)
Abstract The enhancement of patient’s visit to hospital led to the increasing of length of queue particularly at registration division. This condition made the long duration of waiting time for patients. Hospital’s management should manage the patients queue especially for the period of bottle neck condition. This operation research reviewed the patients queue at existing outpatient registration service system and proposed the optimal system based on queuing theory and trade-off analysis of cost of service and cost of waiting. Cross-sectional data applied to collect the patient’s arrival rate, service time for every server, waiting cost, and queue related behavior. Result of this study suggested that existing system was non-steady state system and not optimum based on trade-off analysis. Patients who came at least 08.00 am should serve with 2 servers of queue number service, and 6 servers of outpatient registration. Whereas patients who came after 08.00 am should serve with 1 servers of queue number service, and 2 servers of outpatient registration. This study recommended the range of patient’s arrival and service rate that the describe viability of optimum system. This study suggested hospital’s management should be focus on manage the patient arrival at early morning with applied the suitable queue management technology to controlling the registration waiting line.AbstrakPeningkatan kunjungan pasien ke rumah sakit menyebabkan antrian pasien khususnya pada pelayanan rawat jalan bertambah. Kondisi ini menyebabkan waktu tunggu pelayanan menjadi lama. Manajemen rumah sakit sebaiknya mengelola antrian pasien terutama pada pelayanan yang mengalami hambatan (bottle neck). Penelitian operasional ini bertujuan mengkaji antrian pasien pada sistem pelayanan pendaftaran rawat jalan dan merekomendasikan sistem yang optimal berdasarkan analisis dengan teori antrian dan trade-off antara biaya pelayanan dengan biaya menunggu per pasien. Pengumpulan data secara potong lintang untuk mengetahui tingkat kedatangan pasien, tingkat pelayanan tiap loket pelayanan, dan perilaku pasien saat mengantri. Hasil penelitian menunjukkan sistem pelayanan yang ada saat ini dalam kondisi tidak steady state dan tidak optimum berdasarkan analisis trade-off. Direkomendasikan untuk mengoperasikan 2 loket pengambilan nomor antrian dan 6 loket pendaftaran rawat jalan bagi pasien yang datang sebelum jam 08.00, serta mengoperasikan 1 loket pengambilan nomor antrian dan 2 loket pendaftaran rawat jalan bagi pasien yang datang setelah jam 08.00. Pada studi ini peneliti juga merekomendasikan rentang tingkat kedatangan pasien dan tingkat pelayanan yang dapat diterapkan untuk sistem yang optimal. Disarankan agar manajemen rumah sakit memfokuskan pengelolaan kedatangan pasien dan antrian pasien pada pagi hari, dengan menerapkan teknologi pengelolaan atrian yang sesuai.